EFFICACY OF PERCUTANEOUS DRAINING OPERATIONS FOR SIMPLE RENAL CYSTS - Sarychev, L.P.; Sarychev, Y.V.; Pustovoyt, A.L.; Suprunenko, S.M.; Savchenko, R.B.; Ustenko, R.L.; Sukhomlyn, S.A. (World of Medicine and Biology, 2021)
The relevance of the work is due to the fact that the choice of the optimal method for minimally invasive treatment of simple renal cysts is controversial and there is no consensus. In order to assess the effectiveness of treatment, we carried out both a retrospective and prospective analysis of the documentation of 455 patients with simple renal cysts. Percutaneous draining operations performed in 402 (88.4 %) patients followed by sclerotherapy with 96 % ethanol have proven to be an effective treatment for progressive (>6 cm) and symptomatic simple renal cysts. Bosniak category II simple renal cysts are characterized by a significant increase in drainage time. Symptomatic parapelvical, multichambered, intraparenchymatous (Bosniak category IIF-III) and complicated (Bosniak category IV) simple renal cysts should be a subject for “open” surgical treatment.